2007
DOI: 10.1016/j.devcel.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-Mediated Transport of Smad2 Is Required for Signaling in Response to TGF-β Ligands

Abstract: During vertebrate development, Activin/Nodal-related ligands signal through Smad2, leading to its activation and accumulation in the nucleus. Here, we demonstrate that Smad2 constantly shuttles between the cytoplasm and nucleus both in early Xenopus embryo explants and in living zebrafish embryos, providing a mechanism whereby the intracellular components of the pathway constantly monitor receptor activity. We have gone on to demonstrate that an intact microtubule network and kinesin ATPase activity are requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 38 publications
4
67
4
Order By: Relevance
“…Uncontrolled elevated CDK1 inhibits chromatid separation via phosphorylation of separase. Demonstration of TGF-␤-mediated mitotic regulation unravels a previous mystery in which mitotic regulator is down-regulated in response to TGF-␤ signaling (Choi et al, 1999;Wan et al, 2001) and further explains the presence of activated Smad2/3 detected during mitosis (Batut et al, 2007), which advances our understanding of TGF-␤ biology.…”
Section: A New Physiological Role For Tgf-␤ In Regulatingmentioning
confidence: 91%
See 1 more Smart Citation
“…Uncontrolled elevated CDK1 inhibits chromatid separation via phosphorylation of separase. Demonstration of TGF-␤-mediated mitotic regulation unravels a previous mystery in which mitotic regulator is down-regulated in response to TGF-␤ signaling (Choi et al, 1999;Wan et al, 2001) and further explains the presence of activated Smad2/3 detected during mitosis (Batut et al, 2007), which advances our understanding of TGF-␤ biology.…”
Section: A New Physiological Role For Tgf-␤ In Regulatingmentioning
confidence: 91%
“…Recent studies have suggested a potential involvement of the Smad cascade in regulating the cellular mitotic apparatus (Batut et al, 2007). To examine the effect of TGF-␤ signaling in the regulation of mitosis, we determined the effect of the presence of activated Smad3 on mitosis by biochemical and immunocytochemical analyses.…”
Section: Activation Of Smad3 Mediates Tgf-␤ Signaling In Mitosismentioning
confidence: 99%
“…The same study used a heterokaryon assay to demonstrate the shuttling ability of Smad2 and to map the export activity to a region comprising the linker and MH2 domain. Fluorescence perturbation and photoactivation experiments with GFP-fusions of Smad2 have, more recently, provided direct visual proof of the continuous exchange between the nuclear and the cytoplasmic pools of Smad2 both in tissue culture cells, in tissue explants of Xenopus laevis embryos, and in whole living zebrafish embryos [21][22][23]. Thus there is compelling evidence that Smad2 and 4 continuously shuttle between the cytoplasm and the nucleus in unstimulated cells.…”
Section: Evidence For Smad Nucleocytoplasmic Shuttlingmentioning
confidence: 94%
“…The most likely explanation is that continuous nucleocytoplasmic shuttling of Smads, even in actively signaling cells, which are in a state of maximal nuclear Smad accumulation, connects events at the plasma membrane with the nucleus. This notion has now been directly demonstrated by photobleaching and photoactivation experiments using GFP fusions of Smad2 and 4 [21][22][23].…”
Section: Evidence For Smad Nucleocytoplasmic Shuttlingmentioning
confidence: 98%
“…For western blotting, embryos were snap-frozen at stage 10 and processed as described (Batut et al, 2007). We used rabbit anti-pSmad2 (Cell Signaling, 1/1000), mouse anti-Smad2 (BD Biosciences, 1/1000) and mouse anti--tubulin (Sigma, 1/10,000) antibodies.…”
Section: Quantitative Rt-pcr and Western Blottingmentioning
confidence: 99%